2011
DOI: 10.1152/ajpgi.00528.2010
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation modulates intestinal smooth muscle phenotype in vitro and in colitis in vivo

Abstract: Intestinal inflammation causes an increased intestinal wall thickness, in part, due to the proliferation of smooth muscle cells, which impairs the contractile phenotype elsewhere. To study this, cells from the circular muscle layer of the rat colon (CSMC) were isolated and studied, both in primary culture and after extended passage, using quantitative PCR, Western blot analysis, and immunocytochemistry. By 4 days in vitro, both mRNA and protein for the smooth muscle marker proteins α-smooth muscle actin, desmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 32 publications
6
57
0
Order By: Relevance
“…Despite the persistence of these changes, the contractile response of smooth muscle cells was normal at this time (35). By contrast, expression of contractile proteins continues to deteriorate in the in vitro environment, as they are cultured repeatedly (16). These differences suggest that, within the environment of the intact colon, the epigenetic mechanisms more or less reset after inflammatory injury to ensure normal function.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Despite the persistence of these changes, the contractile response of smooth muscle cells was normal at this time (35). By contrast, expression of contractile proteins continues to deteriorate in the in vitro environment, as they are cultured repeatedly (16). These differences suggest that, within the environment of the intact colon, the epigenetic mechanisms more or less reset after inflammatory injury to ensure normal function.…”
Section: Discussionmentioning
confidence: 96%
“…Most studies have confirmed the contractile phenotype of cultured gut smooth muscle cells by demonstrating that they express smooth muscle-specific contractile proteins by immunostaining (17,19,27). Some studies found reduced expression of select contractile proteins in colon (17) and vascular (18) smooth muscle cells but did not investigate the alterations in expression of the cell-signaling proteins involved in excitation-contraction coupling; the contractile proteins receive signals from the cascade of cell-signaling proteins activated during excitation-contraction coupling telling them to contract. These signals, initiated by binding of an agonist, such as ACh, to M 3 receptors in gut smooth muscle cells, define the profile of contraction, such as amplitude and duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inflammation-induced thickening of the circular and longitudinal muscle layers could be explained by several mechanisms, including hypertrophy and/or secretion of inflammatory cytokines, which are considered to have mitogenic effects on muscle cells (46,50,62). In line with these reports, muscle thickening after HI in our animal model was accompanied by increased cell numbers and cell proliferation within the muscle layers of the fetal intestine and elevated mRNA levels of IL-1b and IL-17, two proinflammatory cytokines that are known to promote intestinal muscle growth (50).…”
Section: Discussionmentioning
confidence: 99%